1994
DOI: 10.1677/joe.0.1420435
|View full text |Cite
|
Sign up to set email alerts
|

A novel hypothyroid 'growth-retarded' mouse derived from Snell's dwarf mouse

Abstract: This paper describes a novel mutant mouse that has been spontaneously derived from the Snell's dwarf (DW/J) mouse. It was named the 'growth-retarded mouse' because of a characteristic growth pause followed by the delayed onset of pubertal growth. The onset of the increase in pituitary GH content that normally occurs concomitant with pubertal growth was also delayed in the growth-retarded mice. The serum concentration of thyroxine was very low in these mice from the neonatal period through adulthood, and a supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 0 publications
3
40
0
Order By: Relevance
“…T 3 replacement restores growth retardation (Yoshida et al 1994) and serum TSH levels (Tomita et al 1995) in grt mice. Thyroid hormone receptor a (TRa) and TRb mRNA and protein have been detected in pancreatic islets (Zinke et al 2003).…”
Section: Tpst2mentioning
confidence: 95%
See 3 more Smart Citations
“…T 3 replacement restores growth retardation (Yoshida et al 1994) and serum TSH levels (Tomita et al 1995) in grt mice. Thyroid hormone receptor a (TRa) and TRb mRNA and protein have been detected in pancreatic islets (Zinke et al 2003).…”
Section: Tpst2mentioning
confidence: 95%
“…Normal phenotype (C/C or C/grt) and grt (grt/grt) male mice were obtained by mating wild (C/C) or heterozygous (C/grt) female mice with grt male mice. These mice were initially obtained as the offspring born to a pair of phenotypically normal siblings of DW/J strain mice and were distinguished on the basis of their body weights as described elsewhere (Yoshida et al 1994). Animals were studied at 2-12 months of age, and all experimental procedures were performed in accordance with the Institutional Guidelines for Animal Care and Use of Saitama University.…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we concluded that the infertility in grt female is due to a thyroid hormone deficiency. The growth-retarded (grt) mouse has an autosomal recessive, fetal-onset, severe thyroid dysgenesis related to thyroid-stimulating hormone (TSH) hyporesponsiveness [20,41]. We identified that the grt phenotype is caused by a single misssense mutation in the tyrosylprotein sulfotransferase 2 (TPST2) gene with a C-to-G transition at nucleotide 798, leading to the replacement of a highly conserved histidine with glutamine at codon 266 in the sulfotransferase domain by positional cloning [36].…”
mentioning
confidence: 99%